Properties of non-standard fly ash – slag cements containing calcareous fly ash - Katarzyna Synowiec (Budownictwo i Architektura, 2013)
The paper presents the tests results of the properties of non - standard fly ash - slag cements composition. Both natural (unprocessed) and activated by grinding calcareous fly ash was used. It was found that the calcareous fly ash next to the granulated blast furnace slag may be a component of low - clinker cements (ca. 40%). Those cements are characterized by low heat of hydration and overdue of initial setting time in comparison with Ordinary Portland Cement, moreover they have an unfavorable effect on consistency and its upkeep in time. Production of fly ash - slag cements is possible for strength class 32,5 N when the component of cement is raw fly ash, and for strength classes 32,5 N, 32,5 R and 42,5 N when ground fly ash was used. Fly ash activated by grinding was characterized by higher activity.